Fazlur Rahman's Hermeneutic Analysis of Hamka's Tafsir al-Azhar - Rahmah Eka Saputri (Islamic Thought Review, 2023)
Tafsīr al-Azhar by HAMKA is a work of Malay tafsīr that exists to answer social problems in the Indonesian context in the era when HAMKA lived. Therefore, contextualization is the dominant feature in HAMKA's interpretation; it is considered in line with Fazlur Rahman's double movement hermeneutic principle. This research is a literature review analyzing Tafsīr al-Azhar by HAMKA using Fazlur Rahman's double movement hermeneutic perspective to find compatibility between the two. In general, this research finds that, in Tafsīr al-Azhar, HAMKA applies Fazlur Rahman's double movement hermeneutic method; especially when he attempts to get in and answer current issues by taking the main Qur'an principles through the intertextuality process and exploring the sociohistorical setting of a verse.